Responding to social isolation among older adults through lifelong learning: Lessons and questions during COVID-19. Issue 1 (2nd January 2020) - Talmage, Craig A.; Baker, Abby Lehr; Guest, M. Aaron; Knopf, Richard C.
ABSTRACT: As local systems shift to meet their constituents' needs during the COVID-19 pandemic, lifelong learning institutes showcase positive responses to addressing the older adults' needs. Older adults have not only greater susceptibility to contracting COVID-19; they also are at higher risk of social isolation and its adverse health outcomes. During COVID-19, the quarantine and distancing procedures can exacerbate social isolation. As local communities seek to bolster their residents' well-being during COVID-19, older adults cannot be overlooked. This essay shares brief coverage of the issue of social isolation among older adults to set up a discussion of the response of a lifelong learning provider in Maricopa County, Arizona, USA. This essay uses the Osher Lifelong Learning Institute at Arizona State University as an exemplary case in addressing older adults needs, specifically community and learning needs, during the COVID-19 pandemic. The essay concludes with questions for future research and practice.